The Psychological Condition of Parents with Children Addicted to Glue: Emotional Tension and Parental Guilt - Malsya, Regi; Sujadi, Eko; Indra, Syaiful; Wahyudi, Iqmal (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Adolescent glue addiction is a deviant behavior that adversely affects not only adolescents but also their parents, often leading to severe psychological distress. This study aims to explore the psychological conditions of parents with glue-addicted children, focusing on emotional strain and parental guilt. Employing a qualitative narrative approach, the research involved four parents from Kerinci Regency, Jambi, whose children exhibited glue addiction behaviors. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that parents experience considerable psychological distress, with emotional strain manifesting as stress, sleep disturbances, anxiety, and feelings of hopelessness. Parental guilt is reflected in self-blame, perceived failure in parenting, and prolonged internal conflict. These psychological challenges negatively influence parents’ daily functioning and their relationships with their children. The study underscores the need for psychological support, particularly family counseling that incorporates supportive and narrative approaches, to assist in emotional regulation, enhance parent–child communication, and restore parental self-efficacy. Overall, the findings provide a basis for developing guidance and counseling programs that integrate family-centered interventions in addressing adolescent addiction cases.